Impact of His bundle pacing on right ventricular performance in patients undergoing permanent pacemaker implantation - Grieco, Domenico; Bressi, Edoardo; Curila, Karol; Padala, Santosh K; Sedlacek, Kamil; Kron, Jordana; Fedele, Elisa; Ionita, Oana; Giannuzzi, Sara; Fagagnini, Alessandro; Panattoni, Germana; De Ruvo, Ermenegildo; et al. (Pacing and clinical electrophysiology, 2021)
BACKGROUND: His-Bundle pacing (HBP) is an emerging technique for physiological pacing. However, its effects on right ventricle (RV) performance are still unknown. METHODS: We enrolled consecutive patients with an indication for pacemaker (PM) implantation to compare HBP versus RV pacing (RVP) effects on RV performance. Patients were evaluated before implantation and after 6 months by a transthoracic echocardiogram. RESULTS: A total of 84 patients (age 75.1±7.9 years, 64% male) were enrolled, 42 patients (50%) underwent successful HBP, and 42 patients (50%) apical RVP. At follow up, we found a significant improvement in RV-FAC (Fractional Area Change)% [baseline: HBP 34 IQR (31-37) vs. RVP 33 IQR (29.7-37.2),p = .602; 6-months: HBP 37 IQR (33-39) vs. RVP 30 IQR (27.7-35), p < .0001] and RV-GLS (Global Longitudinal Strain)% [baseline: HBP -18 IQR (-20.2 to -15) vs. RVP -16 IQR (-18.7 to -14), p = .150; 6-months: HBP -20 IQR(-23 to -17) vs. RVP -13.5 IQR (-16 to -11), p < .0001] with HBP whereas RVP was associated with a significant decline in both parameters. RVP was also associated with a significant worsening of tricuspid annular plane systolic excursion (TAPSE) (p < .0001) and S wave velocity (p < .0001) at follow up. Conversely from RVP, HBP significantly improved pulmonary artery systolic pressure (PASP) [baseline: HBP 38 IQR (32-42) mmHg vs. RVP 34 IQR (31.5-37) mmHg,p = .060; 6-months: HBP 32 IQR (26-38) mmHg vs. RVP 39 IQR (36-41) mmHg, p < .0001] and tricuspid regurgitation (p = .005) irrespectively from lead position above or below the tricuspid valve. CONCLUSIONS: In patients undergoing PM implantation, HBP ensues a beneficial and protective impact on RV performance compared with RVP.
Keywords: Female; pacemaker; Ventricular Dysfunction, Right; Hisův svazek; mužské pohlaví; Humans; kardiostimulace umělá; kardiostimulátor; Cardiac Pacing, Artificial; echocardiogram; Bundle of His; tepový objem; lidé; His-Bundle pacing; right ventricle; senioři; Stroke Volume; conduction system pacing; ženské pohlaví; dysfunkce pravé srdeční komory; Aged; Pacemaker, Artificial; Male